2015
DOI: 10.1080/00219266.2015.1058842
|View full text |Cite
|
Sign up to set email alerts
|

Recontextualising Cellular Respiration in Upper Secondary Biology Education. Characteristics and Practicability of a Learning and Teaching Strategy

Abstract: Since concepts may have different meanings in different contexts, students have to learn to recontextualise them, i.e. to adapt their meanings to a new context. It is unclear, however, what characteristics a learning and teaching strategy for recontextualising should have. The study aims to develop such a learning and teaching strategy for cellular respiration. The strategy consists of a storyline, consisting of three contexts, with embedded cognitive elements and some episodes focussed on recontextualising ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(6 reference statements)
0
11
0
4
Order By: Relevance
“…Research has suggested that possibly central to all of these is that students often associate respiration with breathing, making it difficult to conceptualize the cellular mechanisms involved in energy transformation ( 20 ). This deeper understanding of the molecular mechanisms that comprise respiration requires students to coordinate knowledge of biological organization on multiple levels ( 21 ). Such connections are often difficult for students and could contribute to the persistence of misconceptions in STEM learning ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that possibly central to all of these is that students often associate respiration with breathing, making it difficult to conceptualize the cellular mechanisms involved in energy transformation ( 20 ). This deeper understanding of the molecular mechanisms that comprise respiration requires students to coordinate knowledge of biological organization on multiple levels ( 21 ). Such connections are often difficult for students and could contribute to the persistence of misconceptions in STEM learning ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in the current study allow a comparison with the strategy for recontextualising 'cellular respiration' (Wierdsma 2012;Wierdsma et al 2016). First of all, there are some resemblances.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Unfortunately, the analysis of the data was delayed when an adapted design of an LT-strategy was available and tested in school practice. In the meantime, a study on recontextualising 'cellular respiration' was conducted (Wierdsma 2012;Wierdsma et al 2016). That means that, after completing the analysis of the current study, it is possible to compare both LT-strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Guzdial [5] argued also for the use of multiple contexts, as he stated that "the only way to achieve decontextualized knowledge is to teach beyond a single context" (p. 6). Likewise, existing research in biology education [14] indicated that using a concept in different contexts facilitates transfer.…”
Section: Recontextualizationmentioning
confidence: 99%
“…As a first step, we investigated how students recognize what algorithm to use in a certain context, what elements in a context support determining what algorithm is appropriate to use, and what similarities between contexts play a role in this process. Although research has been carried out on transfer and recontextualization [8,14], to our knowledge, no studies have been found which focus on recontextualization of algorithmic thinking. This work in progress explores students' strategies for recognizing abstract concepts in application situations to be able to apply an algorithm in a given situation.…”
Section: Introductionmentioning
confidence: 99%